1987
DOI: 10.1093/oxfordjournals.eurheartj.a062325
|View full text |Cite
|
Sign up to set email alerts
|

Restenosis and its determinants in first and repeat coronary angioplasty

Abstract: KEY WORDS: PTCA, restenosis, repeat PTCA, PTCA outcome determinants. (PTCA) Since its introduction' 12 ' successful percutaneous long-term success of PTCA. Reported restenosis transluminal coronary angioplasty (PTCA) has rates (14-47%) vary, depending in part on the denbeen shown to relieve angina and myocardial nition used, but according to the larger series' 18 " 22 ', ischaemia as assessed by exercise electrocardiogone patient in three with successful PTCA must raphy 13 ', thallium scintigraphy* 3 ' 4 ', … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Restenosis is a major complication that occurs after percutaneous transluminal coronary angioplasty (PTCA) in about 30-32% of patients and after intracoronary stent placement in 12-32% of patients (Weiczorek and Tsongalis 2001;Rapold et al 1987;Serruys et al 1994Serruys et al , 1998Sigwart et al 1987). Some differences exist in the mechanism involved in this phenomenon in PTCA and stenting.…”
Section: Introductionmentioning
confidence: 99%
“…Restenosis is a major complication that occurs after percutaneous transluminal coronary angioplasty (PTCA) in about 30-32% of patients and after intracoronary stent placement in 12-32% of patients (Weiczorek and Tsongalis 2001;Rapold et al 1987;Serruys et al 1994Serruys et al , 1998Sigwart et al 1987). Some differences exist in the mechanism involved in this phenomenon in PTCA and stenting.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment strategies are coronary artery bypass grafting, percutaneous transluminal coronary angioplasty (PTCA), and intracoronary stent. However, after PTCA, restenosis occurs in about 30 to 32% of patients and after intracoronary stent placement in 12 to 32% of patients [2][3][4][5][6]. Substantial differences exist in the mechanisms of restenosis between conventional PTCA and stenting.…”
Section: Introductionmentioning
confidence: 99%
“…A number of separate studies have found that percentage residual stenosis is an important factor in restenosis even after taking other factors into account using multivariate regression analysis. [11][12][13][14][15][16][17] Similarly, our study demonstrated that a stent-like result was a predictive factor for reducing restenosis.…”
Section: Restenosismentioning
confidence: 75%